PENGEMBANGAN MODEL PEMBELAJARAN DIGITAL LITERASI “SCIENCE” MELALUI PENDEKATAN SAINTIFIK BERBASIS PROYEK PADA PEMBELAJARAN IPA DI SMP - Posumah, Irvanda; Taunaumang, Heinrich; Rengkuan, Mariana (PT. Antis International Publisher, 2024)
The primary characteristics of 21st-century learning emphasize the importance of digital literacy in preparing individuals to manage information, collaborate, and adapt to rapid changes in the digital society. A project-based digital literacy learning model is crucial as it equips students with necessary skills to navigate effectively in an increasingly interconnected digital world through authentic projects integrating digital technology, enabling them to learn, innovate, collaborate, and communicate effectively in a continually evolving global context. This development study aims to produce a valid, practical, and effective